Pelatihan Wirausaha Pembuatan Sabun Mandi bagi Karang Taruna di Kelurahan Kemlayan Serengan Surakarta - M. Yunan Hidayat; Muhammad Irfan Marzuqi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
The growth of many new businesses the growth of many new businesses among teenagers is expected to provide benefits to the surrounding community. These benefits can be in the form of financial and non-financial benefits. The financial benefits of entrepreneurship can be in the form of economic independence obtained in running a business, while non-financial benefits are in the form of growing a resilient and unyielding mentality in the face of life difficulties, distancing oneself from wrong associations, and utilizing time in positive and productive activities. Based on these problems, it is necessary to hold entrepreneurship training for the younger generation, especially mosque teenagers, to foster the entrepreneurial spirit of the mosque teenagers. By holding the training, it is hoped that it will be able to explore creative business ideas. and have a positive effect on the mental development of the younger generation. In this case, the training is specifically aimed at teenagers of The An Nikmah Mosque, Kemlayan Kemlayan, Serengan District, Surakarta City. This community service is carried out in several steps involving field research methods in the form of: 1) Identification of problems carried out as a first step to formulate what will be used as material for training materials in this service activity, 2) Conducting a field survey to the Kelurahan Kemlayan as the place where the activity is carried out, 3) Then conducting an interview and discussion process with the Kelurahan, Karang Taruna and Takmir mosques to identify problems in soap making training. The implementation of community service programs in order to produce maximum results, it is necessary to have stages. There are 3 (three) stages that need to be classified, namely the preparation stage, the implementation stage, and the evaluation stage.